Impact of adverse environmental conditions on the fatigue behavior of carbon epoxy adhesive joints under mode II fracture - Paula Vigón; Jaime Viña; Miguel Lozano; Antonio Argüelles (Scientific Reports)
Abstract This work analyses how environmental degradation affects the behaviour of adhesive joints in carbon-epoxy composites. These joints, made from a unidirectional carbon fibre-reinforced epoxy matrix and bonded with an epoxy-based adhesive, were tested under mode II fracture static and fatigue loading conditions. The experimental analysis was carried out using the End Notched Flexure (ENF) test method to evaluate both the fatigue initiation phase (G-N curves) and the fatigue crack growth phase (G-da/dN curves). Specimens were subjected to controlled exposure in a salt spray chamber and a climatic chamber (hygrothermal) with different exposure periods: no exposure, 1 week, 2 weeks, 4 weeks and 12 weeks. Fatigue initiation data were analysed using a probabilistic Weibull distribution model. Key findings reveal that environmental degradation significantly reduces the fatigue resistance of the adhesive joints. Under static loading, the load capacity of the adhesive joints decreased by approximately 20% after saline exposure and 25% after hygrothermal exposure. Additionally, fatigue crack growth rates were found to change depending on the type and duration of environmental exposure, underscoring the critical role of environmental conditions on joint behaviour.